2017
DOI: 10.1152/ajpcell.00235.2016
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin improves intestinal barrier function: modulation of intracellular signaling, and organization of tight junctions

Abstract: Association between circulating lipopolysaccharide (LPS) and metabolic diseases (such as type 2 diabetes and atherosclerosis) has shifted the focus from high-fat high-cholesterol containing Western-type diet (WD)-induced changes in gut microbiota per se to release of gut bacteria-derived products (e.g., LPS) into circulation due to intestinal barrier dysfunction as the possible mechanism for the chronic inflammatory state underlying the development of these diseases. We demonstrated earlier that oral supplemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
124
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(134 citation statements)
references
References 28 publications
5
124
3
2
Order By: Relevance
“…Furthermore, the increased concentrations of pro-inflammatory cytokines such as TNF-α, IL.-1β and IL-6 in C. jejuni infected co-cultures were down-regulated after curcumin treatment [99]. These results indicate that curcumin in competition to TLR-4 binding antagonized local and systemic inflammatory responses triggered by bacterial LPS/LOS [99,100]. Moreover, it has been reported that the competition between curcumin and LPS/LOS to bind TLR-4 inhibited the MyD88-dependent pathway [101].…”
Section: Activation Of Tlr-4 Signaling By C Jejuni Lipooligosaccharimentioning
confidence: 86%
“…Furthermore, the increased concentrations of pro-inflammatory cytokines such as TNF-α, IL.-1β and IL-6 in C. jejuni infected co-cultures were down-regulated after curcumin treatment [99]. These results indicate that curcumin in competition to TLR-4 binding antagonized local and systemic inflammatory responses triggered by bacterial LPS/LOS [99,100]. Moreover, it has been reported that the competition between curcumin and LPS/LOS to bind TLR-4 inhibited the MyD88-dependent pathway [101].…”
Section: Activation Of Tlr-4 Signaling By C Jejuni Lipooligosaccharimentioning
confidence: 86%
“…Similarly in NAFLD mice model, treatment with resveratrol enhances barrier function by increasing mRNA expression of TJ proteins ZO-1, occludin, and claudin-1 in the intestinal mucosa [144]. Curcumin also modulates intestinal barrier integrity and attenuates paracellular permeability and organization of TJs [145]. Thus, targeting TJ proteins, which maintain intact intestinal epithelia, is another area of therapeutic approach for the control of intestinal permeability in cirrhosis and HCC.…”
Section: Targeting Gut Epithelial Barrier To Prevent Hccmentioning
confidence: 99%
“…The innate immune system in the small intestine is comprised of both a physical barrier of intestinal epithelial cells (IECs) and their biochemical products, and an underlying and complementary immunological barrier [49]. The physical barrier is often considered to include intestinal alkaline phosphatase, a loose layer of mucus [50], tight junctions linking IECs, and antimicrobial proteins (AMPs) released by a specialized lineage of IECs, Paneth cells [51].…”
Section: Innate Immune Systemmentioning
confidence: 99%